پەرەسەندنی بەدامەزراوەیی بوونی دەسەڵاتی سیاسی لە باشوری کوردستان پێش ڕاپەڕینی ساڵی ١٩٩١ - الدین, پ. د. سردار قادر محی; عبدالكریم, م. ی. ئومێد عبدالقادر (Sulaimani Journal for Humanities, 2023)
The Kurdish nation is one of the oldest nations that existed between the two rivers and its surroundings in the region. This means that the Kurds have an ancient history. This nation has practiced a form of independence and statehood at some historical periods; it had political power. However, for many times it was ruled by nations and states that ruled the region. For this purpose, we want to focus on the development of the institutionalization of political power among the Kurdish nation in South Kurdistan before uprising. The first objective of our research is to present the historical hierarchy that the form of institutions and the process of institutionalization of Kurdish political power in South Kurdistan has gone through. Because history has always been a strong factor in the identification and development of political phenomena. In fact, the process of institutionalizing political power is a difficult and complex process, especially for developing societies, which do not have deep experience in administration; They have not yet been able to properly embody this process. Therefore, our research aims to answer the following questions: What were the forms and methods of political power in South Kurdistan before the uprising? What are the stages of the development of the process of institutionalization of Kurdish political power? According to these questions, we assume that the institutionalization of Kurdish political power in South Kurdistan has been dominated by tribal and individual forms at many stages; However, after the July 14 revolution in Iraq, the Kurds have been able to institutionalize political power, especially in the revolutionary movement, and then transfer this experience to formal and collective work. For this purpose, we have used each of the methods (historical), to present the stages of the development of Kurdish political power. We have also used the method of analytical description to describe the forms of institutionalization of political power in South Kurdistan, as well as to analyze the process of institutionalization of political power before the 1991 uprising. Then we came to the conclusion that the process of institutionalization of political power in South Kurdistan has not been as necessary. In history, tribalism and individualism have prevailed. But after the 1960s there was a good effort and a begging for the establishment of political power has been established.
Keywords: Political power; institutionalization process of political power; South Kurdistan; Mesopotamian administration